Mineralization of LCFA associated with anaerobic sludge: kinetics, enhancement of methanogenic activity, and effect of VFA - Pereira, M. A. (2004)
Long-chain fatty acids (LCFA) associated with anaerobic sludge by mechanisms of precipitation, adsorption, or entrapment can be biodegraded to methane. The mineralization kinetics of biomass-associated LCFA were established according to an inhibition model based on Haldane’s enzymatic inhibition kinetics. A value around 1,000 mg COD-LCFA g VSS-1 was obtained for the optimal specific LCFA content that allowed the maximal mineralization rate. For sludge with specific LCFA contents of 2838 ± 63 and 4571 ± 257 mg COD-LCFA g VSS-1, the specific methanogenic activities in the presence of acetate, butyrate, and H2/CO2 were significantly enhanced after the mineralization of the biomass-associated LCFA. For sludge with a specific LCFA content near the optimal value defined by the kinetic model, the effect of adding VFA to the medium was studied during the mineralization of the biomass-associated LCFA. Different patterns were obtained for each individual substrate. Acetate and butyrate were preferentially consumed by the consortium, but in the case of propionate no evidence of a sequential consumption pattern could be withdrawn. It was concluded that LCFA do not exert a bactericidal neither a permanent toxic effect toward the anaerobic consortia. A discussion is addressed to the relative roles of a reversible inhibitory effect and a transport limitation effect imposed by the LCFA surrounding the cells.